Ultrafiltration behavior of partially retained proteins and completely retained proteins using equally‐staged single pass tangential flow filtration membranes. (27th July 2018) - Arunkumar, Abhiram; Zhang, Junyan; Singh, Nripen; Ghose, Sanchayita; Li, Zheng Jian
Abstract : This work examines the ultrafiltration behavior of partially retained proteins like lysozyme and completely retained proteins like monoclonal antibodies using single pass tangential flow filtration (SPTFF) modules with different screen channels and molecular weight cut‐offs. When the staging of the SPTFF used the same membrane area in each stage, there was no impact of the module screened channel or the buffer matrix on the final concentration achieved for completely retained monoclonal antibodies. A hybrid configuration containing 30 kDa membranes and 50 kDa membranes increased the maximum achievable concentration for both the monoclonal antibodies used in this work, at the same time, allowing a two‐fold to four‐fold increase in normalized feed flow‐rate through the system compared to only the 30 kDa or only the 50 kDa membranes. The sieving coefficient of lysozyme measured and calculated using SPTFF was lower than those measured during conventional recirculation TFF indicating a more complicated concentration polarization effect than conventional recirculation TFF. Moreover, the sieving coefficients of lysozyme were the same for the 10 kDa regenerated cellulose and 50 kDa PES membranes while it was higher for the 30 kDa regenerated cellulose membrane. The difference in TFF and SPTFF behavior is important when the product of interest is desired to be permeated. This work presents the first body of data for partially and completely retained solutes together in the SPTFF mode and provides a strategy to increase protein concentration at higher feed flow rates. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 2018 © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:1137–1148, 2018